2018
DOI: 10.1080/17454832.2018.1473453
|View full text |Cite
|
Sign up to set email alerts
|

Art therapy and underlying fMRI brain patterns in military TBI: A case series

Abstract: TBI and PTSD are global issues and are often referred to as signature wounds of the Iraq and Afghanistan wars. Art therapy can provide unique insights into military service members' injuries and states of mind via externalisation within an art product; however, interpretation of results is complex and subjective. Advance neuroimaging tools such as resting state fMRI can be employed to demonstrate objective measures of brain structure and activity. This case series highlights two distinct patient profiles, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Most studies to date have focused on relatively healthy populations but these tools are particularly relevant in research involving the treatment of psychological trauma. It is now common knowledge that central nervous system and neurobiological mechanisms of stress response and memory recall are compromised as a result of traumatic experiences and that the creative process offers an opportunity to rework and repair fragmented memories within an attuned therapeutic relationship (Walker et al, 2016, 2018; King, 2019). It is possible to consider that learning new sensory-motor associations when experiencing the same sensory input and associating these with a different output can help overwrite traumatic memories, which can be measured and tested with this innovative technology (King, 2018).…”
Section: Potential Approaches To Research In Art Therapy Using Mobimentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies to date have focused on relatively healthy populations but these tools are particularly relevant in research involving the treatment of psychological trauma. It is now common knowledge that central nervous system and neurobiological mechanisms of stress response and memory recall are compromised as a result of traumatic experiences and that the creative process offers an opportunity to rework and repair fragmented memories within an attuned therapeutic relationship (Walker et al, 2016, 2018; King, 2019). It is possible to consider that learning new sensory-motor associations when experiencing the same sensory input and associating these with a different output can help overwrite traumatic memories, which can be measured and tested with this innovative technology (King, 2018).…”
Section: Potential Approaches To Research In Art Therapy Using Mobimentioning
confidence: 99%
“…Lastly, although not mobile, positron emission tomography and functional magnetic resonance imaging studies could examine structural as well as functional outcomes of art therapy. For example, Walker et al (2018) found correlations between visual themes of social connectedness and improved thalamic functioning in patients diagnosed with post-traumatic stress. Changes in amygdala and hippocampal volume might be other structural changes to track in combination with functional brainwave shifts seen during art making assessed through MoBI.…”
Section: Potential Approaches To Research In Art Therapy Using Mobimentioning
confidence: 99%
“…In the case of the masks, Walker and her team found that service members with higher PTSD scores were more likely to depict psychological injury and trauma whereas those with lower PTSD scores were more likely to depict themes that suggested a sense of community, such as patriotic images. In collaboration with NICoE's neuroimaging department, they conducted a pilot study using fMRI to study brain activity in 10 service members with chronic mild traumatic brain injuries (7). Service members who had depicted injury and trauma in their masks had less activity in a neural network known as the task-free default mode network, which tends to be active during periods of low stimulation-hence, suggesting that their minds were less at ease when at rest.…”
Section: Facing Your Fearsmentioning
confidence: 99%
“…We have since seen the development of research on a wide range of approaches to art therapy which keep art making and viewing as central, such as Carr and Hancock (2017), Coles, Harrison, and Todd (2019), Huet (2017), Kalmanowitz (2016) and Walker, Stamper, Nathan, and Riedy (2018), to name but a few. In order to reflect the centrality of the art in contemporary art therapy, our editorial board recently appointed the journal's first photo editor.…”
Section: Editorialmentioning
confidence: 99%